2015
DOI: 10.1103/physrevb.92.195401
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the 0.7 anomaly and the Kondo effect: Geometric crossover between a quantum point contact and a Kondo quantum dot

Abstract: Quantum point contacts (QPCs) and quantum dots (QDs), two elementary building blocks of semiconducting nanodevices, both exhibit famously anomalous conductance features: the 0.7-anomaly in the former case, the Kondo effect in the latter. For both the 0.7-anomaly and the Kondo effect, the conductance shows a remarkably similar low-energy dependence on temperature T , source-drain voltage V sd and magnetic field B. In a recent publication [F. Bauer et al., Nature, 501, 73 (2013)], we argued that the reason for t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
3
29
1
Order By: Relevance
“…For larger values of B we obtain the plateau of m(B) corresponding to the saturated polarization. A similar dependence of magnetization on the external magnetic field was reported by Heyder and coauthors [76] for SIAM model and for Kondo quantum dot. The dot energy (ε d ) dependence of the linear conductance for several values of magnetic field strength and for T = 0 is presented in Fig.…”
Section: B the Effect Of Magnetic Fieldsupporting
confidence: 85%
“…For larger values of B we obtain the plateau of m(B) corresponding to the saturated polarization. A similar dependence of magnetization on the external magnetic field was reported by Heyder and coauthors [76] for SIAM model and for Kondo quantum dot. The dot energy (ε d ) dependence of the linear conductance for several values of magnetic field strength and for T = 0 is presented in Fig.…”
Section: B the Effect Of Magnetic Fieldsupporting
confidence: 85%
“…The first one is a zero-bias anomaly (ZBA), which is present, when B≠0 and remains approximately constant when |B| is increased. Different explanations have been proposed for the zero-bias conductance peak close to the 0.7 G 0 anomaly including the formation of a spontaneous spinpolarisation [49,51], quasi-bound states leading to a Kondo impurity [48,50,52] and ferromagnetic spincoupling [53]. We attribute the ZBA to a local magnetic impurity that develops in atomic contacts of some transition metal elements, even in clean contacts, as a result of the reduced dimensionality [54,55].…”
Section: Resultsmentioning
confidence: 74%
“…However, this precondition has been put into question, particularly for clean QPCs. More recent works following this type of argument have appeared [11][12][13]19].…”
Section: Kondo Physics In a Qpcmentioning
confidence: 99%
“…Since the 0.7 structure is observed to disappear with lower temperatures they ascribed this behaviour to the Kondo effect (in addition to the presence of a zero-bias conductance peak). Further investigations suggested that the 0.7 anomaly and ZBA share certain similarities with the Kondo effect in quantum dots [12,13].…”
Section: Kondo Physics In a Qpcmentioning
confidence: 99%
See 1 more Smart Citation